THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING AND SPEECH DEVELOPMENT IN CHILDREN 6-12 MONTHS - Setiawan, Fiona; Herwanto, Herwanto (HEARTY, 2024)
Exclusive breastfeeding without additional foods is related to the distribution of nerves in speech development. When the breastfeeding process is repeated, it can train the child’s voice-forming muscles and mouth structure. An interesting problem is that previous research shows that there is no relationship between exclusive breastfeeding and children’s speech development. The assessment used is Denver II. This study aimed to assess the speech development of normal or suspected children. The sample was carried out by purposive sampling. The number of respondents in this study was 141 people, 75 boys (55.3%) and 66 girls (45%). Exclusive breastfeeding data was obtained for 105 respondents, of whom 89 respondents (84.8%) had normal speech development, and 16 respondents (15.2%) were suspect. Meanwhile, 36 respondents were not given exclusive breast milk, 30 respondents (83.3%) had normal speech development and 6 respondents (16.7%) were suspect. A statistically insignificant relationship between exclusive breastfeeding and the speech development of children aged 6-12 months at Puskesmas Grogol Petamburan, Jakarta Barat with a p-value of 1,000 (p>0.05). This research involves various factors that can influence speech development apart from exclusive breastfeeding, so further research is needed to identify factors that can influence children’s speech development.